VP60 The Importance Of Patient Organizations Involvement In Health Technology Assessment. (2017) - Apostolidis, Kathi; Makaroff, Lydia; De Lorenzo, Francesco; Florindi, Francesco
Abstract : INTRODUCTION: In Europe, the work done by the European Commission and the European Network for Health Technology Assessment (EUnetHTA) has consolidated the role of Health Technology Assessment (HTA), and promises to better harmonize its impact across European Union (EU) countries. However, more work is needed to improve patient involvement in assessing new health technology, and in developing research priorities. METHODS: The European Cancer Patient Coalition (ECPC) developed a model for engagement of patients in HTA based on the experience from: ECPC's 'Value of Innovation in Oncology' White Paper, which includes input from ECPC's membership ECPC's leading role in the Patient Preferences in Benefit-Risk Assessments during the Drug Life Cycle (PREFER) study, funded by the Innovative Medicines Initiative, to develop guidelines on how patient-preference studies should be performed throughout the development of new medical treatments. RESULTS: The ECPC 'Value of Innovation in Oncology' White Paper was launched in 2017. The paper provides ECPC's policy position on key obstacles to equitable access to meaningful innovation. The paper recommends the establishment of an EU-wide HTA body to reduce delays and variations in access and to avoid duplication of effort by individual Member States. The paper also recommends that patients should be formally and routinely included in HTA policy and operations at EU and at national levels. These recommendations were also submitted to the European Commission's public consultation on strengthening EU cooperation on HTA. Through its work in PREFER, ECPC is helping to improve how patient preferences are measured and valued to capture the impact of health technology on patients daily life. Patient preferences are concerned with measuring how patients value components such as treatment end points, route of administration, treatment duration, treatment frequency, frequency of side-effects, price, and quality of life. CONCLUSIONS: Patient organization involvement in HTA is vital. Patient organizations offer unique insights, experiences, identify unmet needs, and can help to produce practical recommendations